MAPPING RESEARCH PRODUCTIVITY OF BIOINFORMATICS SCHOLARLY COMMUNICATION DURING 2010 TO 2019: A SCIENTOMETRIC STUDY - MURUGANANDHAM, Mr.N.; P.SIVARAMAN (International Journal of Psychosocial Rehabilitation, 2020)
The present paper explains the Mapping Research Productivity of Bioinformatics scholarly Communication during 2010 to 2019: A Scientometric Study. The data analyzed the Scopus Database and searching key word of Bioinformatics. The study reveals the year wise publications, analyze the Relative Growth Rate and Doubling Time, Top ten Prolific Authors, Top Ten Rank Subject Area, Document Type, Source Title, Country wise publications and keyword search. The result analyzed the year wise publications in year 2019 more number of publications 15394 (16.32%), Among the 10 year’s period of Research Growth trend has research increase from 0.63 in 2011 and 0.18 in 2019 and doubling time during increased from 1.09 to 4.21 in 2018. Author “Chen, G” contributed 109 publications (15.08%) is more numbers, Top Ten Rank Subject Area an Agricultural and Biological Sciences (10.63%) secured as a first position, majority an “Articles” (61.42%) contributed in the Bioinformatics research.